1978
DOI: 10.1073/pnas.75.10.4935
|View full text |Cite
|
Sign up to set email alerts
|

Reaction to phytotoxins in a potato population derived from mesophyll protoplasts

Abstract: Alternaria solani, the causal agent of early blight disease in potato, produces two host-specific, li idlike toxins in culture. Both compounds are required in tgie leaf bioassay for the elicitation of typical early blight symptoms, but the compounds are individually inactive. The procedures for the preparation of both compounds are outlined. These compounds can be used effectively to select for toxin-insensitive and sensitive clones of a Russet Burbank potato cultivar that have been regenerated from single mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

1979
1979
1999
1999

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(29 citation statements)
references
References 6 publications
0
28
1
Order By: Relevance
“…With wheat (Triticum aestivum), only a very few plants have been obtained sporadically from wheat cultures derived from various organs (Shimada et al 1969;Dudits et al 1975). Stable, regenerated plants in wheat should be possible, since disease-resistant plants of maize (Gengenbach et al 1977) and potato (Matern et al 1978), and herbicide-resistant plants of tobacco (Chaleff and Parsons 1978) have been obtained by tissue culture techniques.…”
Section: Efficient Differentiationmentioning
confidence: 99%
“…With wheat (Triticum aestivum), only a very few plants have been obtained sporadically from wheat cultures derived from various organs (Shimada et al 1969;Dudits et al 1975). Stable, regenerated plants in wheat should be possible, since disease-resistant plants of maize (Gengenbach et al 1977) and potato (Matern et al 1978), and herbicide-resistant plants of tobacco (Chaleff and Parsons 1978) have been obtained by tissue culture techniques.…”
Section: Efficient Differentiationmentioning
confidence: 99%
“…Mycelial plugs (10 mm in diameter) of the isolate of Ppn grown on oatmild agar were placed in 500 ml flasks, containing 100 ml specific liquid medium that is suitable for most Phytophthora species (10). The flasks were kept in incubator at 28 oc in dark for 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…The IR spectrum showed absorption bands at 3200 cm -1 due to a hydroxyl group and at 1720 cm -1 due to a carbonyl group and at 1600 cm -1 due to a phenyl group. 3.90 (3H, s) attributable to a methoxyl group, it was deduced that the phytotoxin had a closely related structure to that of zinniol (2), which has been isolated from the phytopathogenic fungus Alternaria zinniae. SI Extensive comparison between zinnolide (1) and zinniol (2) by the 'H NMR spectrum revealed that two hydroxymethyl groups in 2 were completely missing in 1. fnstead, the presence of a lactol moiety (15 6.60, IH, O-CHOCO) was deduced in zinnolide 2.…”
Section: Received April 19 1985mentioning
confidence: 99%
“…3.90 (3H, s) attributable to a methoxyl group, it was deduced that the phytotoxin had a closely related structure to that of zinniol (2), which has been isolated from the phytopathogenic fungus Alternaria zinniae. SI Extensive comparison between zinnolide (1) and zinniol (2) by the 'H NMR spectrum revealed that two hydroxymethyl groups in 2 were completely missing in 1. fnstead, the presence of a lactol moiety (15 6.60, IH, O-CHOCO) was deduced in zinnolide 2. In fact, reduction of 1 with LiAIH4 in ether afforded a diol, whose spectral data were completely identical with those of authentic (2) in all respects.…”
Section: Received April 19 1985mentioning
confidence: 99%
See 1 more Smart Citation